ORGANIZING INTERACTIVE LESSONS BASED ON PAINTING AND VISUAL ARTS - Boboqulova Adiba Husanovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the use of painting and visual arts as a foundation for organizing interactive lessons in education. Interactive teaching methods enhance student engagement, promote creativity, and develop critical thinking skills. By integrating painting and visual arts into lesson planning, teachers create a dynamic learning environment that encourages collaboration, problem-solving, and active participation. The article discusses various strategies for using visual arts to facilitate interactive learning, including group projects, visual analysis, and creative assignments. The findings indicate that incorporating painting and visual arts into interactive lessons significantly improves students’ cognitive, social, and aesthetic development.